Pain in Huntington’s disease and its potential mechanisms - Li, Jiajie; Wang, Yan; Yang, Riyun; Ma, Wenjun; Yan, JunGuo; Li, Yi; Chen, Gang; Pan, Jingying (Frontiers in Aging Neuroscience, 2023)
Pain is common and frequent in many neurodegenerative diseases, although it has not received much attention. In Huntington’s disease (HD), pain is often ignored and under-researched because attention is more focused on motor and cognitive decline than psychiatric symptoms. In HD progression, pain symptoms are complex and involved in multiple etiologies, particularly mental issues such as apathy, anxiety and irritability. Because of psychiatric issues, HD patients rarely complain of pain, although their bodies show severe pain symptoms, ultimately resulting in insufficient awareness and lack of research. In HD, few studies have focused on pain and pain-related features. A detailed and systemic pain history is crucial to assess and explore pain pathophysiology in HD. This review provides an overview concentrating on pain-related factors in HD, including neuropathology, frequency, features, affecting factors and mechanisms. More attention and studies are still needed in this interesting field in the future.